STUDI KELAYAKAN USAHA BUDIDAYA GURAMI DENGAN MEDIA KOLAM JARING APUNG (Studi Kasus di Dusun Combongan, Desa Jambidan, Banguntapan, Bantul, Daerah Istimewa Yogyakarta) - , MUCHAMMAD FAIZIN, Dr. Henry Yuliando, STP, MM, M.Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Jambidan Village, Sub-district of Banguntapan, Bantul Regency, DIY, is a village well known as the production center of gurami, especially the fingerlings. In this village also existed a lot of mudholes ex-brick quarry unused. Otherwise, the problem faced by farmers such as predators and diseases both by the factors of bacteria and environment. Another problem is the farmers assume that gurami farm as the sideline bussiness because it needs time about one year. At the same time, the demand of gurami in Yogyakarta could not be fulfilled by its own farmers. The purpose of this study is to applicate the cultivation of gurami with pool floating nets as the solutions of above problems and test the feasability both technology and finance. Based on the study result, it can be formulated that the cultivation of gurami with pool floating nets could be the solution of the cultivation that need the length of time, predators, and diseases. Moreover, this business is feasible to be done both technology and finance.